Clinical and methodological considerations for psychological treatment of cognitive impairment in major depressive disorder. Issue 4 (July 2020) - Douglas, Katie M.; Milanovic, Melissa; Porter, Richard J.; Bowie, Christopher R.
Abstract : Background: Cognitive impairment is considered a core feature of major depressive disorder (MDD) and research into psychological treatments aiming to address cognitive impairment are gaining momentum. Compared with the well-established research base of cognitive treatment trials in schizophrenia, including meta-analyses, mood disorder research is much more preliminary. Aims: To focus on identifying the important factors to consider in developing larger-scale psychological treatment trials targeting cognitive impairment in mood disorders. Trial design recommendations have been published for cognitive treatment trials in bipolar disorder. Method: An in-depth discussion of methodological considerations in the development of cognitive treatment trials for MDD. Results: Methodological considerations include: screening for, and defining, cognitive impairment; mood state when cognitive intervention begins; medication monitoring during cognitive interventions; use of concomitant therapy; level of therapist involvement; duration and dose of treatment; choice of specific cognitive training exercises; home practice; improving adherence; appropriate comparison therapies in clinical trials; and choice of primary outcomes. Conclusions: As well as guidance for clinical trial development, this review may be helpful for clinicians wanting to provide cognitive interventions for individuals with MDD.